Students’ semantic reasoning characteristics on solving double discount problem - Lydia Lia Prayitno; Purwanto Purwanto; Subanji Subanji; Susiswo Susiswo; Ninik Mutianingsih (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2022)
Semantic is associated with the relationship between symbol, reference, and the problem’s context involved in the problem-solving process which also involves reasoning and decision-making. Hence, this study describes the characteristics of students’ semantic reasoning to solve the double discounts problem. 51 high school students in Sidoarjo participated in this qualitative study. The data were collected through 15-20 minutes problem-solving tests. The students' answers were grouped into correct and wrong answers. The correct answers were then regrouped once more based on the strategies used by the students to answer the test and to identify their semantic reasoning characteristics. The data were analyzed by reducing, classifying the think-aloud and observing. Then the similarity of characteristics of students' semantic reasoning when solving the double discount problem was identified. To test the accuracy of the data, triangulation method was used. This semantic reasoning was identified by (1) giving the problem situation, (2) stating the keywords and their meaning, (3) stating the relationship, (4) transforming it into a mathematics statement, (5) calculating based on their strategies, (6) decision making, and (7) completing the answer interpretation. This study contributes to developing basic knowledge in interpreting each process of solving ill-structured problems until finding a solution.